Production of Sausage from Macabí Fish Pulp (2018)
The objective of this study is to promote healthy eating habits through the production of sausage made from fish. The study uses a qualitative approach with a descriptive scope and an active participation research design, using participative observation and focus group techniques. The study’s findings are that both the participants and the community involved in discussions on the product found it to be viable and liked it. Additionally, through workshops, awareness was raised and information was shared on the changes in eating habits required to promote a healthy culture.